Simultaneous thoracic and abdominal donation after circulatory death organ recovery: the abdominal surgeon's perspective. Issue 2 (3rd April 2023) - Thiessen, Carrie; Wisel, Steven A.; Roll, Garrett R.
Abstract : Purpose of the review: To summarize the international experience with heart-liver (joint) donation after circulatory death (DCD) procurements and to explore the technical challenges in joint abdominal and thoracic DCD procurement. Recent findings: Following completion of the Donors After Circulatory Death Heart Trial in the US, combined thoracic and abdominal DCD is poised to become the standard of care, expanding access to life-saving heart and lung allografts. DCD heart procurement relies on collection of donor blood for priming of the normothermic perfusion pump, which delays cooling of abdominal organs and increases risk of ischemic injury. We review the effect of donor ischemia time on abdominal organs, with several proposed technical solutions to optimize transplant outcomes for all organs. Summary: The strategies reviewed in this manuscript may inform clinical decision-making, preoperative coordination between thoracic and abdominal procurement teams, and surgical technique for joint DCD procurements. Several approaches to organ procurement organization (OPO) and national policy, as well as future areas of focus for research are proposed.